Urinary organophosphate metabolite levels in Palestinian pregnant women: results of the Middle East Regional Cooperation Project - Abdeen, Ziad; Berman, Tamar; Azmi, Kifaya; Abu Seir, Rania; Agha, Hazem; Ein-Mor, Eliana; Göen, Thomas; Stein, Yael; Richter, Elihu; Calderon-Margalit, Ronit (International Journal of Environmental Health Research, 2016)
The purpose of the study was to measure urinary organophosphate (OP) metabolites in Palestinian pregnant women, and to compare levels with those in pregnant women in Jerusalem and women from the general population in Israel. We measured six dialkyl phosphates in urine samples collected from 148 pregnant women from the West Bank area. Median total dimethyl phosphate (DMtotal) levels were significantly lower in Palestinian women compared to Jerusalem pregnant women and women in Israel (p = 0.041). In Palestinian women reporting that their place of residence was near an agricultural field, DMtotal levels were significantly higher (p = 0.037). Lower urinary excretion of dimethyl phosphate pesticide metabolites in Palestinian women compared to Israeli women may result from lower consumption of fruits and vegetables in the Palestinian population. Our findings highlight differences in OP pesticide exposure in populations with close geographical proximity but with differences in culture, diet, lifestyle, and regulatory oversight of pesticides.
EVALuna2:9744